Cooperative-Problem Based Learning Model Design in Online Learning - Syahrul Ramadhan; Atmazaki Atmazaki; Vivi Indriyani; Elfia Sukma (Fakultas Bahasa dan Seni UNP, 2023)
At this time, online learning is commonplace, although there are still limitations. Needs analysis reveals that individual learning predominates and that cooperative learning is difficult to implement, despite its significance. Based on this, the purpose of this research is to develop a Cooperative-Problem Based Learning model to be used as a distance learning model in learning Indonesian for high school students. This type of research uses the Plomp Model for development (preliminary research; prototype stage; and assessment stage). This study uses a descriptive data analysis approach. The data was obtained based on the validation results that have been carried out in 2 ways, namely self-evaluation and expert validation. Validation was carried out using instruments in the form of a questionnaire and the results of the questionnaire analysis were analyzed using descriptive statistics. The results showed that the teaching materials produced were classified as very valid and could be tested on students. The results of the study show that a language learning model is needed that allows students to learn cooperatively in groups even when distance or online learning is used. In addition, the learning model must adapt to the demands of students and develop following the progress of science and technology. A possible alternative is the Cooperative-Problem-Based Learning approach.